The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1046/j.1365-2257.2001.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Placing the newborn on the maternal abdomen increases the volume of umbilical cord blood collected

Abstract: Haematopoietic stem cell transplantation is an important therapy for certain haematological and malignant disorders. Umbilical cord blood contains a high proportion of potentially transplantable haematopoietic progenitor cells. However, the use of cord blood stem cell transplantation is limited by the low number of stem cells obtainable from a single cord blood donor. The aim of our study was to investigate the possibility that procedures during delivery might influence the number of umbilical cord blood haema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…These results are consistent with most of the previous reports (Donaldson et al 1999;Yamada et al 2000;Li et al 2001;George et al 2006;Mancinelli et al 2006), including that meconium in the amniotic fluid correlates with better cell counts (Askari et al 2005). Therefore the total LD cells per CB unit analyzed in the present study can be assumed as a substitute variable instead of the total nucleated cells in some previous studies (Lasky et al 2002;Mohyeddin Bonab et al 2004;Solves et al 2005), and can be also confirmed by other previous studies (Pafumi et al 2001;Bornstein et al 2005). In addition, the univariate analyses also show the significantly positive correlations between neonatal birth weight, placental weight, net weight of CB, and gestational age (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with most of the previous reports (Donaldson et al 1999;Yamada et al 2000;Li et al 2001;George et al 2006;Mancinelli et al 2006), including that meconium in the amniotic fluid correlates with better cell counts (Askari et al 2005). Therefore the total LD cells per CB unit analyzed in the present study can be assumed as a substitute variable instead of the total nucleated cells in some previous studies (Lasky et al 2002;Mohyeddin Bonab et al 2004;Solves et al 2005), and can be also confirmed by other previous studies (Pafumi et al 2001;Bornstein et al 2005). In addition, the univariate analyses also show the significantly positive correlations between neonatal birth weight, placental weight, net weight of CB, and gestational age (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…The number of samples is relatively smallscale compared to other data from CB banks. However, although there are some limitations due to the relatively small sample size, some previous studies were also analyzed by using small samples around 100 CB units (Donaldson et al 1999;Yamada et al 2000;Pafumi et al 2001). We therefore believe that our present study is appropriate to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates in the “upper position” group were placed on the maternal abdomen immediately after birth, while those in the “lower position” group were placed on the delivery table, below the maternal introitus. Effects of placing the newborn on the maternal abdomen after delivery are studied in two articles . These teams showed some positive effect in UCB volume, TNCs, and CD34 + cells of upper position compared to lowers.…”
Section: Highlighted Factorsmentioning
confidence: 99%
“…Besides the comparison of in or ex utero collection, seven studies applied a modified UCB collection technique [24,41–46]. In five of these studies it was investigated whether additional in or ex utero perfusion using heparinized NaCl or another anticoagulant resulted in a higher yield of UCB.…”
Section: Resultsmentioning
confidence: 99%
“…One other study compared the influence of position of the infant after birth on the in utero ‐collected UCB volume. When the newborn was kept above the level of the placenta before cord clamping, the harvested volume was significantly higher, compared to a lower position below the level of the placenta, 87·7 ± 14·5 ml vs. 41·7 ± 8·9 ml [24]. With each of the adaptations tested, the researchers were able to enlarge the harvested UCB volume (Table 5) [24,41–46].…”
Section: Resultsmentioning
confidence: 99%